Branding and Tourism in Komodo: Raising Resort Awareness through Instagram Influencer - Limbono, Pricillia; Lolita, Theresia Lavietha Vivrie (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Accommodation’s competitiveness around Labuan Bajo currently drives them to strive after the COVID-19 pandemic to offer a variety of promotions on its products and services to increase brand awareness and expected visits to the super-priority destination on Komodo Island, East Nusa Tenggara. The study aims to explore how Mohini Resort Komodo, of accommodation in Labuan Bajo, performed the influencer marketing strategy for raising brand awareness through Instagram influencers in such a challenging situation. This descriptive and qualitative case study used in-depth interviews and observations to gather the idea. From the viewpoint of the two-step flow theory of communication, this study elaborates on how brands in the travel industry can use the influencer marketing framework to interact with Instagram influencers as online opinion leaders. The findings show that the resort has put into practice an influencer marketing strategy that includes 1) identifying the marketing objective, target market, and definition of success; 2) defining the best campaign strategy; 3) outlining the creative, creator, and content strategy; and 4) defining budget, target, and media planning. This research contributes to an ongoing examination of the framework for companies in the tourism industry to enforce effective influencer marketing.